Ayo Sinau Basa Jawa: Bahan Digital Penunjang Pembelajaran Kosakata Bahasa Jawa Berbasis Multimedia - Ella Rizky Endryanti; Roekhan Roekhan; Primardiana Hermilia Wijayati (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This research aims to develop digital interactive teaching materials entitled